Si-addition contributes to overcoming the strength-ductility trade-off in high-entropy alloys - Wei, Daixiu; Gong, Wu; Tsuru, Tomohito; Lobzenko, Ivan; Li, Xiaoqing; Harjo, Stefanus; Kawasaki, Takuro; Do, Hyeon-Seok; Bae, Jae Wung; Wagner, Christian; Laplanche, Guillaume; Koizumi, Yuichiro; et al. (International journal of plasticity, 2022)
•Si-addition overcomes the strength-ductility trade-off of CoCrFeNi HEA.•Si-addition tunes the plastic deformation mechanism of the CoCrFeNi HEA.•Si-addition enhances yield stress by multiple strengthening mechanisms.•The plasticity mechanism is tuned partially due to the reduced SFE. Face-centered cubic single-phase high-entropy alloys (HEAs) containing multi-principal transition metals have attracted significant attention, exhibiting an unprecedented combination of strength and ductility owing to their low stacking fault energy (SFE) and large misfit parameter that creates severe local lattice distortion. Increasing both strength and ductility further is challenging. In the present study, we demonstrate via meticulous experiments that the CoCrFeNi HEA with the addition of the substitutional metalloid Si can retain a single-phase FCC structure while its yield strength (up to 65%), ultimate strength (up to 34%), and ductility (up to 15%) are simultaneously increased, owing to a synthetical effect of the enhanced solid solution strengthening and a reduced SFE. The dislocation behaviors and plastic deformation mechanisms were tuned by the addition of Si, which improves the strain hardening and tensile ductility. The present study provides new strategies for enhancing HEA performance by targeted metalloid additions.